2006
DOI: 10.1515/bc.2006.148
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the arylhydrocarbon receptor on eugenol- and isoeugenol-induced cell cycle arrest in human immortalized keratinocytes (HaCaT)

Abstract: Fragrances such as eugenol (4-allyl-2-methoxyphenol) and isoeugenol (2-methoxy-4-propenylphenol), naturally found in reasonable quantities in the essential oils of different spices, are not only common causes of contact dermatitis but also known for their antiproliferative actions. Previously, we found a cell cycle arrest and an arylhydrocarbon receptor (AhR)-mediated activation of cytochromes in immortalized keratinocytes (HaCaT) induced by both compounds. In the present study we investigated whether the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…17 In contrast to control cell, which carry the parental (empty) lentiviral expression vector (e.v. ), no AhR protein was detectable in the knockdown (k.d.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 In contrast to control cell, which carry the parental (empty) lentiviral expression vector (e.v. ), no AhR protein was detectable in the knockdown (k.d.)…”
Section: Resultsmentioning
confidence: 99%
“…Lentiviral transduced HaCaT cells, containing either shRNA sequences for AhR silencing or nonsilencing, are described elsewhere. 17 Primary human keratinocytes (i.e., NHEKs) were isolated from foreskin tissue samples by overnight trypsin digestion. The culture medium was a 3 : 1 mixture of Ham's F-12 medium (L-glutamine (2 mM) and penicillin/streptomycin (100 U/ml)) and DMEM (low glucose (1 g/l), L-glutamine (8 mM) and penicillin/streptomycin (100 U/ml)), supplemented with adenine, insulin, fetal calf serum, hydrocortisone, epidermal growth factor and forskoline.…”
Section: Methodsmentioning
confidence: 99%
“…Environmental chemicals, including contact allergens, are known to shift cell-cycle phases (Kalmes et al, 2006) and, although not yet shown for NAT1, some enzymes including those involved in xenobiotic biotransformation (Gilroy et al, 2001) are expressed cell-cycle phase-dependently. Therefore, we first studied NAT1 activities in different cell-cycle phases and further analyzed cell-cycle phase distribution after PPD treatment.…”
Section: Ppd Inhibits Nat1 In Keratinocytes 321mentioning
confidence: 99%
“…30 The vector, harvest of recombinant lentiviral particles, and infection of skin fibroblasts were performed as previously described. 30 HA concentration in the supernatant of human skin fibroblasts was determined by using HA enzyme-linked immunosorbent assay (Corgenix) 5 days after infection and was calculated as ratio of HA and total cellular protein.…”
Section: Lentiviral Shrna Expressionmentioning
confidence: 99%